1999
DOI: 10.1046/j.1365-2249.1999.00922.x
|View full text |Cite
|
Sign up to set email alerts
|

Protective role of NK1.1+ cells in experimentalStaphylococcus aureusarthritis

Abstract: SUMMARYIn a model of Staphylococcus aureus-induced septic arthritis in C57Bl/6 mice we investigated the role of natural killer (NK) cells in the development of disease. Depletion of NK1.1 þ cells was achieved by repeated injections of the PK136 antibody, whereas control mice received an irrelevant monoclonal antibody, O1C5.B2. Both groups of mice then received injections intravenously with 2 × 10 7 live S. aureus LS-1 secreting toxic shock syndrome toxin-1 (TSST-1). The mice were evaluated for 16 days with reg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
33
0

Year Published

2000
2000
2021
2021

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(33 citation statements)
references
References 27 publications
(37 reference statements)
0
33
0
Order By: Relevance
“…Indeed, different from the study by Sun and Metzger, we detected a minimum level of IFN-g in flu-infected lung after S. aureus superinfection (data not shown). Furthermore, to date, NK cells have only been found to contribute to host defense against primary staphylococcal infection (16,34). In contrast, although exaggerated IL-10 responses to streptococcal superinfection in the fluinfected lung was reportedly linked to increased susceptibility (22,35), we did not detect any measurable levels of IL-10 responses to staphylococcal superinfection in the flu-infected lung (data not shown).…”
Section: Discussionmentioning
confidence: 55%
“…Indeed, different from the study by Sun and Metzger, we detected a minimum level of IFN-g in flu-infected lung after S. aureus superinfection (data not shown). Furthermore, to date, NK cells have only been found to contribute to host defense against primary staphylococcal infection (16,34). In contrast, although exaggerated IL-10 responses to streptococcal superinfection in the fluinfected lung was reportedly linked to increased susceptibility (22,35), we did not detect any measurable levels of IL-10 responses to staphylococcal superinfection in the flu-infected lung (data not shown).…”
Section: Discussionmentioning
confidence: 55%
“…The protective role of NK cells was also demonstrated in models of infection with different strains of Salmonella (196)(197)(198). Similarly, NK cells were shown to play a critical protective role against S. aureus in septic arthritis and pulmonary models of infection (199,200). In the later case, an elegant study revealed that H1N1 influenza virus infection leads to weakened NK cell activity, particularly in terms of TNF-α production, rendering the host more susceptible to a secondary lung infection by S. aureus (201).…”
Section: Benefits Versus Disadvantages Of Nk Cell Activation During Bmentioning
confidence: 89%
“…There is increasing evidence that NK cell activation is regulated by the balance between inhibitory and activating signals. In addition, contact-based costimulatory signals derived from activated monocytes, dendritic cells (19), or NKT cells (5) seem to be necessary for early IFN-␥ secretion and thus an appropriate protective innate response in the absence of antigen (46). This in turn may profoundly influence the nature of the adaptive immune response.…”
Section: Discussionmentioning
confidence: 99%